(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the issues of balance between preserving national values and adapting to globalization processes in the preschool education system. The impact of the modern information space, digital technologies and international educational trends on children's education is highlighted. Also, pedagogical mechanisms for the formation of global competencies in children while preserving national culture, native language, traditions and spiritual heritage are scientifically based. The article also develops practical recommendations aimed at ensuring the integration of national and universal values ​​in preschool educational organizations.